Silver diamine fluoride and glass ionomer sealant use in preventing occlusal surface caries for special needs children - Alhayo, Rehab Tahseen (My University, 2019)
Amaç: Bu çalışmanın amacı, özel gereksinimli çocukların yeni süren daimi posterior dişlerinde, oklüzal yüzey çürüklerinin önlenmesinde gümüş diamin fluoridin klinik etkinliğini değerlendirmek ve bir yıllık takip süresince cam iyonomer fissür örtücü ile karşılaştırmaktır.Materyal ve Metod: Bu klinik çalışma, İstanbul, Marmara Üniversitesi Pedodonti nda yaşları 6-14 arasında olan özel gereksinimli yirmi üç çocukta yapıldı. Katılımcılar ayna, künt sond ve DIAGNOdent pen kullanarak muayene edildi. DIAGNOdent değerleri 0-20 arasında olan ve en az iki çürüksüz daimi posterior dişe sahip çocuklar araştırmaya dahil edildi. SDF (%38) ağızda sol taraftaki dişlere uygulanırken, cam iyonomer fissür örtücü (Fuji TRIAGE) sağ tarafa uygulandı. Cam iyionomer fissür örtücülerin retansiyonları, OHI-S ve çürük oluşumu 3-6-12 ay sonra değerlendirildi. Bulgular: 12 ay sonunda toplam 20 çocuk ve 102 diş değerlendirildi. OHI-S sonuçlarının başlangıç ve 12 Ay değerleri arasında istatistiksel olarak anlamlı bir fark bulundu (p = 0,0001). Simonsen’in kriterlerine göre, cam iyonomer fissür örtücü retansiyon oranları %56,36 A (kayıp yok), %27,27 B (parsiyel kayıp) ve %16,36 C (tam kayıp) olarak bulundu. 12 Ayda çürük oranı, SDF için %2,2, cam iyonomer fissür örtücü içim %1,8 olarak belirlendi. 12 aylık takipten sonucunda malzemeler arasında istatistiksel olarak anlamlı bir fark yoktu (p> 0,05). Sonuç: 12 aylık takip sonucunda her iki materyal de, yeni süren daimi posterior dişlerin başlangıç oklüzal çürüklerinin kontrol edilmesinde eşit derecede etkili bulunmuştur.

Aim: The aim of this study was to evaluate the clinical efficacy of silver diamine fluoride in preventing occlusal surface caries in the permanent posterior teeth for special needs children and comparing it with glass ionomer sealant for one-year follow-up. Material and methods: A split-mouth design clinical study was conducted to twenty-three children with special needs at Istanbul, Marmara University, Department of Pediatric Dentistry. The ages were between 6 and 14 years. At least each child had two permanent posterior teeth with DIAGNOdent results between 0-20 were included. Application of (SDF) (38%) on the left side of the mouth and GIS (Fuji TRIAGE) on the other side of the mouth. The retention of GIS, OHI-S, and occurrence of caries was evaluated after 3-6-12 months. Results: A total of twenty children with 102 teeth were evaluated after 12 months. There was a statistically significant difference between the mean of baseline and followed up of OHI-S results (p= 0,0001). The retention rates for GIS were 56,36% A (complete retention), 27,27% B (partial loss), and 16,36% C (total loss) according to Simonsen’ s Criteria. A few numbers of caries on both sides were found after 12-month, 2,2% at the SDF side and 1,8% at the GIS side, and there was no statistically significant difference between the materials after one year of follow up (p> 0,05). Conclusion: As a result of our study, both materials are equally efficient in controlling initial occlusal caries in newly erupting permanent posterior teeth after 12 months follow-up.
Keywords: cam iyonomer fissür örtücü; Çocuk diş hekimliği; glass ionomer sealant; Gümüş diamin fluorid; özel gereksinimli çocuklar; Pediatric dentistry; Silver diamine fluoride; special needs children